Dasatinib: ten years of clinical practice worldwide - K. M. Abdulkadyrov; V. A. Shuvaev; I. S. Martynkevich (Онкогематология)
The article contains results of meta-analysis of experience in use of second-generation tyrosine kinase inhibitors – dasatinib. The results of clinical trials dasatinib therapy in chronic myelogenous leukemia imatinib-resistant or intolerant patients are presented. The dasatinib and imatinib comparative analysis in first-line therapy in newly diagnosed chronic myelogenous leukemia patients are demonstrated. The range and frequency of dasatinib therapy adverse events are analyzed. Toxicities management recommendations are listed. Perspectives of dasatinib therapy cessation in patients with long lasting deep molecular responses – treatment free chronic myelogenous leukemia remissions are descripted. Also, there is an information about dasatinib usage in treatment of Philadelphia-positive acute lymphoblastic leukemia.